A study of the Windows Vista index as an alternative to the big Mac index - Xia, David Ming (2009)
This paper explores the possibility of using Window Vista Home Basic (WVHB) packaged edition (an Intellectual property protected product) as an alternative to the Big Mac (fast-food item) in the construction of a Purchasing Power Parity (PPP) index. It is used to measure currency valuations. A new Window Vista Index (WVI) was developed and analyzed. The WVI is a technical equivalent of the famous Big Mac Index (BMI) in that it calculates PPP exchange rates simply by computing the local currency prices against the US price. With its product superiority, the WVI seeks to address the limitations of the BMI by minimizing the influence of non-tradable inputs, trade effect and product heterogeneity that lead to currency valuation biasness. An in-depth analysis of the G8 and Newly Industrialized Countries was performed. For results validation, sensitivity analysis was conducted as well as a triangulation framework using the Euro and Renminbi (RMB) as alternative base currencies. A direct accuracy test with the BMI against actual exchange rates was also conducted. The result suggests that the WVI is about 39% more accurate than the BMI in exchange rates prediction. To this end, the WVI can be used to better guide international pricing policies for businesses. Finally, the WVI is limited as it potentially factors in transitory exchange rate fluctuations. This is so as it is only collected at one time of a year. Ideally, this can be eliminated through long term data collection, which can be an area for further research.